Risk Factors of Needlestick and Sharp Injuries among Health Care Workers at Sanglah Tertiary Hospital - I Komang Widarma Atmaja; I Made Ady Wirawan; I Ketut Suarjana (Jurnal Berkala Epidemiologi, 2021)
Background: Needlestick and sharp injuries (NSIs) remain one of the main occupational hazards among health care workers (HCWs) that lead to blood-borne pathogen exposure. Purpose: This study examined the risk factors for NSIs among HCWs at a tertiary referral hospital in Bali. Methods: A case-control study was conducted at Sanglah General Hospital, Bali, involving 171 HCWs, divided into 81 cases and 90 control subjects. The sample was selected using a simple random sampling technique. Data were collected using questionnaires and analyzed using multiple logistic regression. Results: The majority of respondents had experienced NSIs once, in the morning shift, and had affected an individual’s hands. The most frequent activity leading to NSIs was giving an injection and most of the situations causing NSIs involved accidental self-action, and recapping needles. Factors associated with the incidence of NSIs were work career or experience of <5 years (p < 0.01; adjusted odds ratio [AOR]=5.04; 95% confidence interval [CI] = 2.04–12.42), non-compliance with working procedures (p = 0.01; AOR = 2.47; 95%CI= 1.26–4.82), female HCWs (p = 0.03; AOR = 2.21; 95% CI = 1.01–4.55), and unsafe workplace conditions (p = 0.04; AOR = 2.23; 95% CI = 1.01–4.92). Conclusion: Personal and environmental factors such as gender, work experience, compliance with working procedures, and workplace conditions are among the risk factors for NSIs. Occupational health and safety policies and programs focusing on the relevant factors, accompanied by adequate supervision, are necessary to reduce the risk of NSIs occurring.